Development of communication and game interface for an electro-oculogram based assistive technology system - Liang, Jiaqun. (2012)
There are many people in the world suffering from severe paralyzed conditions that hinder them from simple daily tasks such as communication. With the retaining of the ability to move their eyes, it is plausible to improve or develop aiding devices to enable their communication. Signals known as Electro-Oculograms (EOG) can be obtained from the movement of the cornea of eyes. These signals can be processed to determine the direction of movement of the eyes and decode the person’s intention. Implementation of a communication system comprising of virtual keyboards that make use of these EOG signals could provide paralyzed people an alternative to communicate to eternal world. In this project, a graphical user interface (GUI) of the virtual keyboard is developed to provide efficient access to characters using 4 directional eye movements. Furthermore, game interfaces that make use of the EOG signals to interact are developed to provide entertainment for relaxation and training.